Model Pembelajaran Sinektik Perspektif Al-Qur’an dan Implementasinya Pada Pendidikan Akidah-Akhlak Bagi Remaja - Asep Maskur (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
The Qur'anic Perspective Synectical Learning Model is a learning model designed and constructed to enhance and develop spiritual, intellectual, emotional, and social creativity. The development and improvement are carried out through a series of activities to optimize the function of all potential possessed, especially hearing, sight, and heart, guided by the principles and instructions of the Qur'an. The purpose of this research is to find out the synectic learning model from the perspective of the Qur'an and its implementation in akidah-akhlak education for adolescents. The method used in this research is a qualitative approach to literature. The findings in this study were obtained through the analysis related to the discourse of the synectic learning model and the theory of Progressivism philosophy. John Dewey believes that Progressivism is a school of education philosophy that is forward-oriented and positions students as one of the subjects of education who have provisions and potential to develop themselves and have the ability to solve various problems faced. This philosophy also believes that every human being, through their different experiences, always wants change, develops, and becomes better. Synectic activities and the philosophy of Progressivism both emphasize that creativity is an essential element in the development of human life. Similarly, the interpretation of the Qur'anic verses, especially Surah al-Nahl verse 78 and Surah Ali Imran verses 190 to 195 about Ulu al-Albâb and. In the view of Ibn Katsir, Sayyid Qutbh, and Quraish Shihab, Ulu al-Albâb, with all its characteristics, has inspired an ideal figure that must be born as a product of a learning process. This research has limitations on the synectic learning model from the perspective of the Qur'an and its implementation in akidah-akhlak education for adolescents, as well as recommendations for further research to conduct research with other learning models.